The place of bibliometrics in the system of information sciences - Voverienė, Ona (Information & Media, 1996)
It is almost universally recognized that the methodology of a scientific branch is an integral, inseparable part of that scientific branch together with its history, theory, and organisation. Until scientific branches are developing their own methodologies, their scientific status and place in the system of sciences remain questionable. The aim of this article is to define the place of bibliometrics in the system of information sciences. Bibliometrics is a formal scientific subdiscipline, including the complexity of mathematical and statistical methods used to analyse the bibliographical characteristics of documents. There is given a review of literature in which this question was discussed. All different arguments are systematized, analysed, discussed, and made into a conclusion. In the meantime, it is impossible to define the place of bibliometrics in the system of information sciences, because bibliometrics is in rapid development and has no strict definitions